Clinical and molecular aspects of 30 patients with late-onset Pompe disease (LOPD): unusual features and response to treatment - Montagnese, Federica; Barca, E.; Musumeci, O.; Mondello, S.; Migliorato, A.; Ciranni, A.; Rodolico, C.; De Filippi, P.; Danesino, C.; Toscano, A. (Journal of neurology, 2015)
Pompe disease is a rare metabolic disorder, due to mutations in the gene encoding acid alpha-glucosidase (GAA), of which infantile and late-onset forms may occur. Aim of the work was to analyze clinical and laboratory data of a cohort of late-onset Pompe disease (LOPD) patients, collected during the last 15 years and to point out unusual phenotypic/genotypic features as well as enzyme replacement therapy (ERT) responses. We diagnosed 30 LOPD patients; at follow-up, they underwent motor, respiratory, cardiac and muscle MRI evaluations. Motor performances were tested by Walton Gardner-Medwin, GSGC and 6MWT tests. Respiratory function was assessed as FVC % in upright/supine position. LOPD presentations were represented by presymptomatic hyperCKemia (37 %), proximal/axial muscle weakness (53 %) and respiratory impairment (10 %). Median diagnostic delay was 8.6 years (±8.8). Atypical features were observed in 4 patients: marked distal muscle weakness and severe hearing loss at onset, as well as leukoencephalopathy and mesial temporal sclerosis during the disease course. By GAA sequence analysis, two causing mutations were detected in 22/30 patients, only one in the remaining 8 subjects. Overall, 29/30 patients harbored the common c.−32−13T>G mutation (2 were homozygous). Two new DNA variations were discovered (c.2395C>G, c.1771C>T). 14 patients received ERT for up to 60 months. Our study confirms LOPD clinical and genetic heterogeneity: atypical features may contribute to expand the clinical phenotype highlighting its multi-systemic nature. A timely diagnosis could allow early ERT start. An accurate follow-up is recommended to evaluate treatment responses.